Optimasi Pemilihan Barang Dagangan bagi Pedagang Keliling dengan Algoritma Genetika - Iryanto Iryanto; Eka Ismantohadi (Jurnal Teknologi Terapan, 2017)
Existence of constraints increases difficulty in choosing the right goods for a seller. Indeed, the seller wants to optimize the profit gained. Due to limitation of capital and maximum capacity, the seller needs a certain strategy to do the selection. Moreover the fact that each goods has its own probability to sell makes the problem becomes more complex. In this paper, the problem is solved using genetic algorithm. The result of simulation is in a good agreement with analytical solution. The simulation of N-goods selection is also given in the paper.